Physical exercise increases involvement of motor networks as a compensatory mechanism during a cognitively challenging task. (31st May 2018) - Ji, Lanxin; Pearlson, Godfrey D.; Zhang, Xue; Steffens, David C.; Ji, Xiaoqing; Guo, Hua; Wang, Lihong
Abstract : Objective: Neuroimaging studies suggest that older adults may compensate for declines in cognitive function through neural compensation and reorganization of neural resources. While neural compensation as a key component of cognitive reserve is an important factor that mediates cognitive decline, the field lacks a quantitative measure of neural compensatory ability, and little is known about factors that may modify compensation, such as physical exercise. Methods: Twenty‐five healthy older adults participated in a 6‐week dance training exercise program. Gait speed, cognitive function, and functional magnetic resonance imaging during a challenging memory task were measured before and after the exercise program. In this study, we used a newly proposed data‐driven independent component analysis approach to measure neural compensatory ability and tested the effect of physical exercise on neural compensation through a longitudinal study. Results: After the exercise program, participants showed significantly improved memory performance in Logical Memory Test (WMS(LM)) ( P  < .001) and Rey Auditory Verbal Learning Test ( P  = .001) and increased gait speed measured by the 6‐minute walking test ( P  = .01). Among all identified neural networks, only the motor cortices and cerebellum showed greater involvement during the memory task after exercise. Importantly, subjects who activated the motor network only after exercise (but not before exercise) showed WMS(LM) increases. Conclusions: We conclude that physical exercise improved gait speed, cognitive function, and compensatory ability through increased involvement of motor‐related networks.